Clinical efficacy analysis of paxlovid in children with hematological diseases infected with the omicron SARS-CoV-2 new variant - Li, Yixian; Liu, Yong; Wen, Luping; Chen, Hui; Wang, Wenqing; Tian, Mengyao; Cheng, Yucai; Xue, Hongman; Chen, Chun (Frontiers in Pediatrics, 2023)
Objective: To summarize the clinical characteristics of children with hematological malignancies co-infected with novel coronavirus and explore the safety and effectiveness of Paxlovid treatment. Methods: From December 10, 2022, to January 20, 2023, the clinical data of children with hematological diseases diagnosed with novel coronavirus infection in the outpatient and emergency department of the Seventh Affiliated Hospital of Sun Yat-sen University were retrospectively analyzed. Results: According to whether to give paxlovid or not, it is divided into group A (paxlovid group) and group B (non-paxlovid group). The length of fever was 1-6 days in group A and 0-3 days in group B. The viral clearance time was shorter in group A than in group B. The inflammatory indexes CRP and PCT were significantly higher in group A than in group B(P<0.05). Twenty patients were followed up for 1 month after leaving the hospital, and there were 5 cases of reappearance of fever, 1 case of increased sleep, 1 case of physical fatigue and 1 case of loss of appetite within 2 weeks. Conclusions: Paxlovid has no apparent adverse reactions in children 12 years old and younger with underlying hematological diseases infected with the new coronavirus. Focusing on the interaction between paxlovid and other drugs is necessary during the treatment.